PENGARUH TINGKAT FREE CASH FLOW TERHADAP INVESTMENT OPPORTUNITY SET PADA PERUSAHAAN MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Ria Lusiana; Firda Mufidah; Nur Habibah (Universitas La Tansa Mashiro, 2016)
The purpose of this study is to find out whether there is an influence of the level of free cash flow on the price of investment opportunity set. This study analyzes the effect of free cash flow on investment opportunity sets. The sample of this study were 11 manufacturing companies listed on the Indonesia Stock Exchange (IDX) from 2012-2015. Data analysis uses statistical calculations of regression analysis and hypotheses using the SPSS 20.0 for Windows program.This study uses the dependent variable investment opportunity set and the independent variable is free cash flow. The results show that free cash flow has a significant effect on the investment opportunity set of manufacturing companies listed on the IDX. This is indicated by t_ (count) = 2.103, and t_table = 1.678 with a correlation coefficient of r_xy = 0,150, which means that between X and Y variables there is a very weak or good correlation value with a regression equation Y = 6725.630 + 0.035X